Pengaruh Fleksibilitas Kerja, Lingkungan Kerja Fisik, dan Kepuasan Kerja Terhadap Komitmen Afektif Pada Karyawan Shopee Express Tambun Selatan - Nabella Nur Afiyah; Tyna Yunita; Muhammad Asif Khan (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of work flexibility, physical work environment, and job satisfaction on affective commitment in Shopee Express Tambun Selatan employees. The research method used is quantitative research, which means that research is used to examine certain populations and samples, data collection using research instruments, quantitative or statistical data analysis, with the aim of testing the hypothesis that has been applied. The sampling technique used is using a saturated sampling technique or the entire population is sampled, while the number of populations in this study is 100 respondents. Data analysis using Smart PLS 4.0 Software and hypothesis testing, namely the T Test and F Test. Based on the results of the path coefficient hypothesis, there is a P-value of 0.0 or <0.5 and a t-statistics value of 2.4 or> 1.96, then it is stated that there is a significant influence between the variables of work flexibility on affective commitment. The P-value of 0.0 or <0.5 and the t-statistics value of the physical work environment has a value of 3.4> 1.96, then it is stated that there is a significant influence between the variables of physical work environment on organizational commitment. The P-value is 0.0 < 0.5 and the t-statistics value for job satisfaction is 4.7 > 1.96, so it is stated that there is a significant influence between the job satisfaction variable and affective commitment.